1993
DOI: 10.1007/bf02253538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on thermal pain threshold in deprived and minimally-deprived habitual smokers

Abstract: Abstract. This study examined the antinociceptive effects ofsmoking in nine habitual smokers under deprived (12 h) and minimally-deprived « 30 min) conditions. Pain threshold for thermal stimuli, heart rate, blood pressure and ratings of mood, arousal, dominance and well-being were assessed before and after smoking a cigarette. Overall, smoking affected all measured variables in the expected direction, leading to increased physiological activity, elevated pain threshold and improved mood. However, most of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…109 Second, analgesic effects of nicotine may differ across experimental pain models (table 1). Although nicotine consistently increases pain thresholds in cold pressor tests, 9,11,13,110 results are inconsistent with heat 108,111,112 or electrical stimulation pain models. 10,12,[113][114][115] Finally, the effects of nicotine may depend on sex.…”
Section: Human Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…109 Second, analgesic effects of nicotine may differ across experimental pain models (table 1). Although nicotine consistently increases pain thresholds in cold pressor tests, 9,11,13,110 results are inconsistent with heat 108,111,112 or electrical stimulation pain models. 10,12,[113][114][115] Finally, the effects of nicotine may depend on sex.…”
Section: Human Studiesmentioning
confidence: 85%
“…10,12,[113][114][115] Finally, the effects of nicotine may depend on sex. Studies of male subjects find that smoking consistently produces analgesia, 9,11,13,112 whereas studies with only or mostly females report negative results. 113,116 In one study involving both sexes, transdermal nicotine increased pain thresholds to electrical stimulation in males but not females.…”
Section: Human Studiesmentioning
confidence: 89%
“…In general, smoking a cigarette increases thresholds to painful stimulation in experimental settings [88][89][90][91]. Nicotine administered to nonsmoking surgical patients shortly before emergence from anesthesia decreases pain scores and morphine utilization [92].…”
Section: Nervous System Effectsmentioning
confidence: 99%
“…Pomerleau and colleagues have shown that smoking a nicotine-containing cigarette increased the pain awareness thresholds in the cold pressor test (Fertig et al, 1986;Pomerleau et al, 1984). Pauli et al (1993) demonstrated that cigarette smoking decreased sensitivity to thermal stimuli. Girdler et al (2005) in their recent study also observed that women smokers had greater threshold and tolerance to ischemic pain than women nonsmokers when pain testing followed rest.…”
Section: Human Studiesmentioning
confidence: 99%